Amazonian psychics, Muppets and the Antichrist. (New Internationalist, 2006)
The article presents views and insights on various topics. The author attributed the Amazon.com Inc.'s Web site's predictive abilities to good software engineering. The book by Tim Cohen entitled "The Antichrist and a Cup of Tea" have emphasized that Charles, Prince of Wales, is the antichrist. Walt Disney Co. has purchased the Muppets.